HIGH FLUORESCENT LYMPHOCYTE COUNT EXAMINATION IN DENGUE HEMORRHAGIC PATIENTS WITH SYSMEX XN-1000 HEMATOLOGY ANALYZER - Budiono Raharjo; Solichul Hadi (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2019)
Sysmex XN-1000 hematology analyzer is an automated 5-part diff analyzer (eosinophils, basophils, neutrophils, lymphocytes, and monocytes). In the calculated area, the type of difference between the Sysmex hematology device and other hematology devices is Immature Granulocyte (IG), Nucleated Red Blood Cell (NRBC), and High Fluorescent Lymphocytes Count (HFLC). The cells calculated in the HFLC area are atypical lymphocytes. In patients with dengue hemorrhagic fever, it is often found atypical lymphocytes called blue plasma lymphocytes. The purpose of this study was to determine the description of HFLC in patients with dengue fever using the hematology analyzer Sysmex XN-1000. A descriptive retrospective study was conducted during April-May 2017. The subjects of the study were adult patients diagnosed with dengue hemorrhagic fever with WHO criteria. Of the 47 samples of Dengue Hemorrhagic Fever (DHF) patients, the average HFLC results were between 2.0-32.3%, which was 11.5%, while the average range of normal HFLC values was between 0.0-1.4% and was 0.3%. In cases of DHF, there is an increase in HFLC. This is likely to be attributed to atypical lymphocyte increase in dengue hemorrhagic fever. Further research with more varied samples still needs to be done.